Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3847/2041-8213/ab6b2d
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Rayleigh–Taylor Instability in an Experiment Simulating a Solar Loop

Abstract: A hoop force driven magnetic Rayleigh-Taylor instability (MRTI) is observed in a laboratory experiment that simulates a solar coronal loop. Increase of the axial wavelength λ is observed when the axial magnetic field increases. This scaling is consistent with the theoretical MRTI growth rate (•) g m r = k B gk 2 2 0 2 0 , which implies that if k is parallel to B 0 (i.e., undular mode), the fastest-growing mode has l p p m r = = k B g 2 8 0 2 0. Unified Astronomy Thesaurus concepts: Magnetohydrodynamics (1964);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…For this same shot, Moser & Bellan (2012) reported a consistent peak current of I=110 kA. Furthermore, a recent study of magnetic RTI by Zhang et al (2020) on the arched plasma loop experiment with similar parameters (a, λ RT =1 cm and κT=2 eV) also supports that the expected minor radius is close to the observation from the images, a∼1 cm. Both in that study and here, the observed RTI is magnetized and driven by the effective gravity associated with a strong lateral acceleration.…”
Section: Discussionsupporting
confidence: 73%
“…For this same shot, Moser & Bellan (2012) reported a consistent peak current of I=110 kA. Furthermore, a recent study of magnetic RTI by Zhang et al (2020) on the arched plasma loop experiment with similar parameters (a, λ RT =1 cm and κT=2 eV) also supports that the expected minor radius is close to the observation from the images, a∼1 cm. Both in that study and here, the observed RTI is magnetized and driven by the effective gravity associated with a strong lateral acceleration.…”
Section: Discussionsupporting
confidence: 73%
“…By operating the bipolar experiment with a relatively small bias magnetic field (axial magnetic field), Zhang et al. (2020) observed RTIs associated with the acceleration provided by the hoop force caused by the current flowing along the arched flux rope. A series of plasma shots was made with different values of bias magnetic field and it was observed that the wavelength λ of the Rayleigh‐Taylor ripples increased with the bias magnetic field strength in a manner consistent with Equation .…”
Section: Discussion Of the Experiments And Their Main Resultsmentioning
confidence: 99%
“…(b) Scaling of Rayleigh‐Taylor wavelength with charge voltage on bias field capacitor (bias field is proportional to this voltage). (c) plot of y = λ ρ g versus square of bias field voltage; compare with Equation (figure credit: Zhang et al., 2020).…”
Section: Discussion Of the Experiments And Their Main Resultsmentioning
confidence: 99%
“…In this scenario, the RTI can generate a localised electric field, inside which electrons may be accelerated to very high energies. Furthermore, recent experiments have attempted to model the RTI in a laboratory simulated coronal loop experiment (Zhang et al, 2020). The authors found that increasing the strength of the axial magnetic field leads to an increase in the instability's wavelength.…”
Section: Rayleigh-taylor Instabilitymentioning
confidence: 99%